The Relationship between Internet Use and Executive Function among Children with Autism Spectrum Disorder - Cai, Zexi. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Child Development.; Advisor: Sara Johnson.; Committee: Eileen Crehan, and Susan Faja.; Keywords: Psychology, and Neurosciences.